HISTORICAL REVIEW OF GNATHODYNAMOMETRIC METHODS USED FOR THE ASSESSMENT OF MASTICATORY FUNCTION - Desislava Konstantinova; Mariana Dimova (Peytchinski Publishing, 2016)
Gnathodynamometric methods prove to be the oldest means available of obtaining an objective quantitative evaluation of masticatory efficiency. On the basis of data collected using these methods static methods were later introduced and in early 20th century functional dynamic methods were first applied. Referring to dental literature records, the authors' objective was to provide a review of available historical facts about the origin, development and application of gnathodynamometers in the study of masticatory function.